دراسة إحصائية تحليلية لكمية الهطول المطري في سوريا خلال الفترة 1990-2002 باستخدام السياقات العشوائية - العلي ابراهيم; العشعوش أيمن; معلا سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر الأمطار من أهم مظاهر الهطل المطري بالإضافة إلى الثلج والبَردَ, وتشكل أهم مصدر للمياه فيها, ولها أثر كبير في حياة الإنسان والحيوان والنبات. وتتصف الأمطار في سوريا بتبيناتها المكانية والزمانية, وتأخذ دورات موسمية ,حيث تتركز في فصل الشتاء, بينما تنخفض في بقية الفصول حتى تنعدم في فصل الصيف, وتحظى المنطقة الساحلية بأكثر كيات هطول, من بقية المناطق, وذلك يعود لعدة أسباب من أهمها: قربها من المسطح المائي, الارتفاع عن سطح البحر, جهة التضاريس, الموقع الجغرافي, موقع المحطة على خط طول وخط عرض ,........... الخ . وتتناول هذة الدراسة تحليل كمية المطر في سوريا خلال الفترة 1990-2002 بواسطة السياقات العشوائية. وأهم النتائج التي توصلنا اليها : 1- تتميز سوريا يتعاقب فترات زمنية كثيرة الأمطار وأخرى قليلة الأمطار, فمن خلال استعراضنا لكمية الأمطار خلال الفترة 1990-2002 في الجدول الملحق, نجد أن الأعوام التالية :1990-1992-1993-1995-2000 تتصف بأقل كمية هطول وذلك عائد لعوامل مناخية من أهمها :انحسار سيطرة المنخفضات الجوية الجبهية القادمة من البحر المتوسط وسيطرة الضغط الجوي المرتفع, بينما تتصف الأعوام 1991-1994 بأعلى كمية هطول, ويعود ذلك إلى: سيطرة المنخفضات الجوية الجبهية القادمة من البحر المتوسط وسيطرة الضغط الجوي المنخفض . 2- وجود دورات مطرية كل أربع سنوات, وهذا ما نلاحظه في الشكل (1) Rain is very important from of falling in Syria in addition to snow and hailstone, and it is the most important source of water in it. It has a great impact on the life of human beings, animals and plants. Rain in Syria is characterized by place and time differences, and it takes seasonal circles, it rises in winter and disappears in summer. The costal region has higher falling amount than the other regions. This fact is due to many reasons, the most important of which are: the closeness to the watery surface, the height from the sea level, the geographic site and the site of the station on the longitude and latitude. This study analyzes the amount of rain in Syria during 1990-2000 by using the random processes. Here are the most important results we have reached: 1- Syria is characterized by alternating periods of heavy rain and little rain. From the demonstration of the amount of rainfall from 1990-2000 in the appendix, we can see that the falling years 1990-1992-1993-1995-2000 are characterized by less rainfall because of many environmental factors, the most important of which are the recede in the domination of the frontal atmospheric depression coming from the Mediterranean sea and the domination of the high atmospheric pressure, which the years 1991 and 1994 are characterized by higher rainfall amount because of the domination of the frontal atmospheric depression coming from the Mediterranean and the domination of lower atmospheric pressure. 2- There are rain circles every four years. That is what we can notice in fig (1).